Framework for Patient Service Queue System for Decision Support System on Smart Health Care - Manaor Hara Pardede, Akim; Mawengkang, Herman; Zarlis, Muhammad; Tulus, T; Maulita, Yani; Fauzi, Achmad; Novriyenni, N (International Journal of Engineering and Technology, 2018)
Improving the service of patient care in hospitals is important for all, prioritizing patient safety in the event of a sudden or catastrophic attack, in which case the priority is to provide services to the patient. In such situations a decision system is needed, in order for the system to be right and not wrong to do a decision because the handling of this issue is closely related to the patient's life. The patient handling technology supports highly smart healthcare technology, which of course is part of the Smart city. The purpose of this research is to get Smart Health Care model with Decision Support System model approach in public health service, where Decision Support System model for Smart Health Care can solve health service problem in order to make maximum service for patientÂ